1992
DOI: 10.1083/jcb.117.6.1351
|View full text |Cite
|
Sign up to set email alerts
|

Malaria sporozoites and circumsporozoite proteins bind specifically to sulfated glycoconjugates

Abstract: Abstract. Circumsporozoite (CS) proteins, which densely coat malaria (Plasmodia) sporozoites, contain an amino acid sequence that is homologous to segments in other proteins which bind specifically to sulfated glycoconjugates. The presence of this homology suggests that sporozoites and CS proteins may also bind sulfated glycoconjugates. To test this hypothesis, recombinant P. yoelii CS protein was examined for binding to sulfated glycoconjugate-Sepharoses. CS protein bound avidly to heparin-, fucoidan-, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 22 publications
5
90
0
1
Order By: Relevance
“…Heterologous expression of ActA in the nonpathogenic species L. innocua allows bacterial internalization in epithelial polarized and nonpolarized cells (Caco-2, MCDK, HeLa, and Vero) but not in COS-1 fibroblasts, suggesting that ActA is sufficient to directly activate an invasion pathway specific for epithelial cells (Suárez et al 2001). The amino-terminal region of ActA is similar to the domain of the Plasmodium falciparum circumsporozoite protein involved in heparate sulfate recognition and hepatocyte binding (Pancake et al 1992;Coppi et al 2007) and it has been shown that the presence of heparan sulfate at the surface of CHO cells is required for the entry of L. monocytogenes in an ActA-dependent manner (Alvarez- Dominguez et al 1997). The in vivo conditions in which the ActA invasion-associated function would be critical for virulence remain to be characterized.…”
Section: Listeria Monocytogenes Entry In Mammalian Epithelial Cellsmentioning
confidence: 90%
“…Heterologous expression of ActA in the nonpathogenic species L. innocua allows bacterial internalization in epithelial polarized and nonpolarized cells (Caco-2, MCDK, HeLa, and Vero) but not in COS-1 fibroblasts, suggesting that ActA is sufficient to directly activate an invasion pathway specific for epithelial cells (Suárez et al 2001). The amino-terminal region of ActA is similar to the domain of the Plasmodium falciparum circumsporozoite protein involved in heparate sulfate recognition and hepatocyte binding (Pancake et al 1992;Coppi et al 2007) and it has been shown that the presence of heparan sulfate at the surface of CHO cells is required for the entry of L. monocytogenes in an ActA-dependent manner (Alvarez- Dominguez et al 1997). The in vivo conditions in which the ActA invasion-associated function would be critical for virulence remain to be characterized.…”
Section: Listeria Monocytogenes Entry In Mammalian Epithelial Cellsmentioning
confidence: 90%
“…Lactoferrin (aa [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] CAVS QPETKCFQRNMRKI/R yoelii CS, apoE, and lactoferrin. Boldface italics indicate amino acid residues of CS protein required for binding to HSPGs (22).…”
Section: Rklrkrllrdaedlqkrla Vmentioning
confidence: 99%
“…Within minutes after intravenous injection into mice, CS accumulates in the space of Disse on the plasma membrane of hepatocyte microvilli (18). Heparinase treatment of liver sections that have been incubated with CS, and other in vitro experiments using hepatocytes and HepG2 cells as targets, demonstrate that CS binds to HSPGs (19,20). The proteoglycan-binding portion of CS (19,21) is region II-plus (22), a stretch of amino acids highly conserved in all species of malaria parasites (23).…”
mentioning
confidence: 99%
“…TRAP and CSP are also contributing to the gliding motility of sporozoites [30][31][32][33]. CSP is also able to bind with other sulfates like heparin or dextrose sulfate and these may inhibit sporozoite infectivity, motility and block an invasion of the hepatocytes.…”
Section: Sulfurmentioning
confidence: 99%